1993
DOI: 10.1677/jme.0.0100171
|View full text |Cite
|
Sign up to set email alerts
|

Changes in progesterone and oestrogen receptor mRNA and protein during maternal recognition of pregnancy and luteolysis in ewes

Abstract: This study characterized changes in levels of mRNA and protein for endometrial oestrogen receptors (ERs) and progesterone receptors (PRs) during luteolysis and maternal recognition of pregnancy. For cyclic and pregnant ewes, endometrium was collected on days 10, 12, 14, or 16 post-oestrus (4 ewes/day for each status) for the measurement of ER and PR mRNA and protein. The amount of receptor mRNA is expressed in relative units above background, measured from radiographs of dot-blot hybridization of total endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 51 publications
8
36
0
2
Order By: Relevance
“…Estradiol up-regulates the ER mRNA levels in endometrium and myometrium of ovariectomized ewes [12,38]. The increases in ER mRNA and PR mRNA levels in this study were similar to those reported in intact cyclic ewes [27,35]. In the present study, the changes in mRNA levels of ER and PR were consistent with the receptor concentrations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Estradiol up-regulates the ER mRNA levels in endometrium and myometrium of ovariectomized ewes [12,38]. The increases in ER mRNA and PR mRNA levels in this study were similar to those reported in intact cyclic ewes [27,35]. In the present study, the changes in mRNA levels of ER and PR were consistent with the receptor concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…An example of this action is the regulation of the expression of their own receptor; the E-receptor complex stimulates both ER and PR gene expression in uteri of several mammalian species, while the P-receptor complex reduces levels of both receptors [4]. This is displayed by the variations in the concentrations of uterine sex steroid receptors [25,31] as well as their respective mRNAs during the estrous cycle of the sheep [27,35].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial hypothesis was that IFNT inhibited expression of ESR1 and OXTR and stabilized PGR in uterine epithelia to extend the period of the P4 block proposed by McCracken [89]. We found that steady-state levels of PGR mRNA were not different between pregnant and cyclic ewes [110]; however, in situ hybridization analysis revealed loss of expression of PGR mRNA and protein in all uterine epithelia by Day 13 of both the estrous cycle and pregnancy but continued expression of PGR mRNA and protein during pregnancy in both uterine stromal and myometrial cells [111]. Given that P4 is the hormone of pregnancy and that PGR are expressed only in stromal and myometrial cells, the concept that progestamedins from stromal cells affect uterine epithelia became important to our studies.…”
Section: Pregnancy and Pregnancy Recognition Signalingmentioning
confidence: 63%
“…Interferon tau (IFNT) is the pregnancy recognition hormone in sheep and other ruminants that acts to silence expression of estrogen receptor alpha (ESR1) and, in turn, oxytocin receptor (OXTR) to prevent development of the luteolytic mechanism that required oxytocin (OXT) from the corpus luteum (CL) and posterior pituitary to induce luteolytic pulses of prostaglandin F 2a (PGF). Thus, IFNT blocks the ability of the uterus to develop the luteolytic mechanism but does not inhibit prostaglandin synthase 2 (PTGS2) or the basal production of PGF during pregnancy [91,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111].…”
Section: Pregnancy and Pregnancy Recognition Signalingmentioning
confidence: 99%
“…Estrogen affects the oxytocin-induced PGF 2α production presumably through the up-regulation of the OTR receptor [46,47]. Estrogen receptor (ER) is up-regulated before luteolysis, which coincides with an increase in OTR [39,48,49]. Progesterone, essential for the maintenance of pregnancy, may also be required for the luteolytic pr oc ess.…”
Section: Biological Properties Of Ifnτ τ τ τmentioning
confidence: 99%